A Structure Equation Model of Strategic Management for Driving Country Economy of Provincial Chamber of Commerce - Chinsiraprapa, Anuchida; Silpcharu, Thanin (Applied Science and Engineering Progress, 2020)
Situations in the present world have been changed so much that they affect the overall economy of the country. Trade competitions are getting higher, causing the uniting of private businesses into Council of Chamber of Commerce, Federations of Thai Industries, Thai Chamber of Commerce, and Provincial Chamber of Commerce. When Provincial Chamber of Commerce is taken into consideration, it is found that some of them are not strong enough. Moreover, there are many management problems caused by executive committee. This study aimed to investigate strategic management and to develop a structure equation model for Provincial Chamber of Commerce. The qualitative data were collected via interviewing experts while the quantitative ones were collected from executive committee and members of Chamber of Commerce via questionnaire. The number of the samples in total was 500. The analysis showed that the developed structure equation model passed the evaluation criteria, and was consistent with the empirical data. Its Chi-square probability level, relative Chi-square value, goodness of fit index, and root mean square error of approximation were 0.209, 1.122, 0.976, and 0.016 respectively.